Influence of acidic catalysts in Hydrothemal Carbonization (HTC) process for synthesis of carbon nanomaterial prepared from horse manure - Siwakron Sangnoi; Sorakit Wettayavong; Napat Kaewtrakulchai; Apiluck Eiad-ua (My University, 2017)
Horse manure (HM), which is a crucial waste material from livestock sector in Thailand.It consists of hemicellulose, cellulose and lignin that has a potential for carbon material production.In this research, carbon material was prepared from horse manure by hydrothermal treatment (HT) at 200ºC for 24 h with improvement of porosity and surface structure by acid catalyst that HNO3, H2SO4, HCl and H3PO4 with ratio of 1, 3 and 5 wt%, respectively.Then, HT char was pyrolysed at 300ºC for 2 h to obtain the carbon nanomaterial.SEM image displayed that HCl catalyst shows highest porosity on char surface.The production yield treated by HCl 5 wt% is approximately 51.44 wt%.FTIR spectrum confirm that the functional group of biomass polymer was decomposed.
Keywords: Carbon fibers; Nanomaterials; Catalysis for Biomass Conversion